Water/Heavy Fuel Oil Emulsion Production, Characterization and Combustion - Alaa, Moalla; Soulayman, Soulayman; Abdelkarim, Taan; Walid, Zgheib (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
In order to produce a water/heavy fuel oil emulsion (W/HFO) with different water contents to cover the daily needs of a fire tube boiler or a water tube boiler, a special homogenizer is designed, constructed and tested. The produced emulsion is characterized and compared with the pure HFO properties. It is found experimentally in fire tube boiler that, the use of W/HFO emulsion with 8% of water content (W0.08/HFO0.92) instead of HFO leads to a saving rate of 13.56% in HFO. For explaining the obtained energy saving the term â€œequivalent heat value (EHV) of the W/HFO emulsionsâ€, defined as the ratio of the W/HFO emulsion net calorific value to the HFO content in the emulsion, is used. Based on direct measurements, provided in this work, it was found that the equivalent heat value (EHV) increases with the water content in the water/heavy fuel oil (W/HFO). It reaches 1.06 times of HFO net calorific value at water content of 22.24%. The obtained, in the present work, experimental results demonstrate the dependence of the emulsion EHV on its water content. These results are in agreement with the results of other authors. Therefore, the contribution of water droplets in the emulsion combustion is verified. It is found experimentally that, the emitted CO, SO2Â and H2S gases from the fire tube boiler chimney decreases by 5.66%. 3.99% and 48.77% respectively in the case of (W0.08/HFO0.92) emulsion use instead of HFO.